2019
DOI: 10.1021/acs.jpcc.9b08286
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes and Decomposition Mechanisms of HMX-Based Cocrystal Explosives at High Temperatures

Abstract: The cocrystallization effect plays a prominent role in improving the performance of energetic materials. A combinational strategy based on density functional tight-binding molecular dynamics (DFTB-MD) simulations and density functional theory (DFT) was used to elucidate the decomposition mechanisms and reaction kinetics of octahydro-1,3,5,7-tetranitro-1,3,5,7-tetrazocine (HMX)-based cocrystal explosives [HMX/N,N-dimethylformamide (DMF) and HMX/bis­(2,4-dinitro-2,4-diazapentane) (DNDAP)] at high temperatures. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The C N(2) and C N(3) bonds are still more sensitive to OEF than other bonds. However, it is found that EFs have almost no effect on the bond length of HMX as shown in Figure S6, which can be attributed to the stronger bonds of HMX than that of CL-20 in the cocrystal (about 42.6 45 $43.6 46 kcal/mol vs. 35.9 15 kcal/mol). To summarize, due to its molecular structure that is liable to deform under EF, CL-20 is more sensitive to EF than HMX.…”
Section: Electric Field Effect In Evolution Of Bond Lengthmentioning
confidence: 93%
See 1 more Smart Citation
“…The C N(2) and C N(3) bonds are still more sensitive to OEF than other bonds. However, it is found that EFs have almost no effect on the bond length of HMX as shown in Figure S6, which can be attributed to the stronger bonds of HMX than that of CL-20 in the cocrystal (about 42.6 45 $43.6 46 kcal/mol vs. 35.9 15 kcal/mol). To summarize, due to its molecular structure that is liable to deform under EF, CL-20 is more sensitive to EF than HMX.…”
Section: Electric Field Effect In Evolution Of Bond Lengthmentioning
confidence: 93%
“…Class-B reactions correspond to ring-opening reactions and intramolecular atom transferring reactions, which are difficult to be analyzed in RMD simulation, and often overlooked. 17,32,44,45 By using our new analytical method described in Section 2, we successfully identified such reactions in the simulations and summarized the ones with highest frequent in Table 3. In order to understand the initial decomposition mechanism of CL-20 comprehensively, we illustrate the identified main primary and These reactions are the dominant reason for the breakage of a large number of C N bonds within CL-20 before its decomposition into NO 2 , as shown in Figure 7.…”
Section: Electric Field Effect In Initial Reaction Mechanismmentioning
confidence: 99%
“…Furthermore, the conformational change, decomposition mechanism, and reaction kinetics of different HMX/DMF and HMX/DNDAP cocrystals at high temperatures have been studied in recent work. The results indicate that the decomposition mechanisms of different HMX-based cocrystals show great dependence on the temperature.…”
Section: Sensitivity Thermal Decomposition and Detonation Propertiesmentioning
confidence: 94%
“…Nitrate ester plasticized polyether (NEPE) propellant is a new type of crosslinked, high-energy, solid propellant which uses polyether polyurethane as a binder, nitrate esters as plasticizers, and is filled with a large amount of the high-energy oxidant, cyclotetramethylene tetranitramine (HMX) [1][2][3]. It also contains a combustion agent, stabilizer, and combustion promoter [4].…”
Section: Introductionmentioning
confidence: 99%
“…H: the heat release of HMX or a mixed system 2. ∆H: actual added heat value of the system with complexes 1 to 5 3. ∆T: the change in the HMX decomposition peak temperature after the addition of complex 1 to 5.…”
mentioning
confidence: 99%